The e-copyright handbook - Pedley, Paul. (London : Facet Pub., 2012)
'The Electronic Copyright Handbook' provides library and information professionals with practical guidance to minimise the risk of copyright infringement.
'This handbook provides library and information professionals with practical guidance to minimize the risk of copyright infringement in the era of information sharing and online collaborative working. The book considers how copyright applies to a wide range of electronic content types including APIs, e-books, blogs, wikis, RSS feeds, e-mails, streaming, podcasts, broadcasts, databases, social networking sites and GUIs. Author Paul Pedley looks at activities which are especially relevant to library and information services such as the lending of electronic content and the mass digitization of content from a library collection, and considers activities undertaken by internet users such as deep linking, filesharing, mashups, and scraping, and the copyright issues associated with those activities. The text draws upon relevant legislation as well as numerous examples of legal disputes and court decisions from the UK, Europe, and the USA. Highly practical, the book is packed throughout with tips, case summaries, sample wording, and in each section it also draws attention to useful resources. Key topics include: the background to e-copyright and the debates arising; the different content types, from APIs to e-books and wikis; the copyright implications of activities such as deep linking, mashups, scraping and selling digital content second-hand; copyright exceptions such as those for fair dealing, library privilege, the making of a temporary copy, visual impairment, and the public interest; licences for e-content such as Creative Commons, open access, and the open government licence, and microlicensing solutions; the Digital Economy Act 2010; rights enforcement measures; the Hargreaves Review of Intellectual Property and Growth.'--Publisher description.
Content types -- Activities -- The copyright exceptions -- Licences -- The Digital Economy Act 2010 -- Enforcement -- The Hargreaves Review.
Includes bibliographical references (p. [185]-189) and indexes.